2014
DOI: 10.1590/0103-8478cr20130738
|View full text |Cite
|
Sign up to set email alerts
|

Tecnologia de aplicação de agrotóxicos no controle de fitonematoides em soja

Abstract: RESUMO O objetivo deste trabalho foi avaliar o efeito de diferentes sistemas de aplicação tratamento de sementes (TS), sulco de semeadura (Sulco) e associação de ambos (TS + Sulco) e tratamentos químicos no controle de Pratylenchus brachyurus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…However, it is important to highlight that control methods complement each other and management is fundamental in order to assure high productivities (MUNKVOLD et al, 2014). Thus, our results demonstrate that the product efficiency depends on many factor and other application technologies may also complement the seeds treatment, such as the application of the product in the plantation furrow (CORTE et al, 2014). Gourd et al (1993) reported that the activity of chemical products on soil causes the direct death of Meloidogyne juveniles, inhibits hatching, reduces mobility of J2's, and provokes disorientation in penetration.…”
Section: Evaluation Of P Brachyurus Specimens Penetrations During Time After Treatment Of Seedsmentioning
confidence: 58%
See 1 more Smart Citation
“…However, it is important to highlight that control methods complement each other and management is fundamental in order to assure high productivities (MUNKVOLD et al, 2014). Thus, our results demonstrate that the product efficiency depends on many factor and other application technologies may also complement the seeds treatment, such as the application of the product in the plantation furrow (CORTE et al, 2014). Gourd et al (1993) reported that the activity of chemical products on soil causes the direct death of Meloidogyne juveniles, inhibits hatching, reduces mobility of J2's, and provokes disorientation in penetration.…”
Section: Evaluation Of P Brachyurus Specimens Penetrations During Time After Treatment Of Seedsmentioning
confidence: 58%
“…Many strategies for the control of these nematodes have been broadly widespread. This includes use of resistant varieties, crop rotation without hosting species and treatment of seeds (ARAÚJO et al, 2012;CORTE et al, 2014). However, the soybean resistant to this species is scarce in the market, and the variety of hosts for crop rotation have been made the Pratylenchus brachyurus root lesions nematode control management difficult (INOMOTO, 2007;SOUZA & INOMOTO, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nematicide application can be via seed treatment [22], in the sowing furrow [23,24], or by leaf spraying [25,26], and its results are variable, suggesting that the application mode can affect plant physiology too. This plant's physiological reaction can be due to the reduction in the phytonematode population or the phytotoxic effects caused by the nematicide, which is not always perceptible to the bare eye.…”
Section: Introductionmentioning
confidence: 99%
“…O Brasil possui uma agricultura amplamente moderna, onde parte da produção está voltada ao cultivo de grãos (CONAB, 2016). Esta produção é ameaçada constantemente por vários fatores, dentre eles, encontram-se os fitopatógenos, onde os nematoides são responsáveis por grande parte das perdas ocorridas (Corte et al, 2014).…”
Section: Introductionunclassified